Attenuated-chattering global second-order sliding mode load frequency controller for multi-region linked power systems - Nguyen, Phan-Thanh; Nguyen, Cong-Trang (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
In this study, a new chattering-free global second-order sliding mode load frequency controller (CGSOSMLFC) is proposed for multi-region linked power systems (MRLPS). Key achievements of this paper include: i) a new CGSOSMLFC is investigated utilizing only output variables; ii) a global steadiness of the MRLPS is ensured by eliminating the hitting phase in traditional sliding mode control (TSMC), and the undesirable high-frequency vacillation marvel in the control signal is efficiently lessened by utilizing the second-order sliding mode control technique. Firstly, a novel estimator is constructed to conjecture the immeasurable state variables of the MRLPS. Then, an estimator-based CGSOSMLFC is synthesized to force the states of the controlled plant into the anticipated switching surface at an instance time and attenuate the chattering phenomenon in the control indication. Additionally, the total MRLPS’s stability analysis is executed by applying the Lyapunov function theory and linear matrix inequality (LMI), confirming the practicability and reliability of the method. Lastly, simulation outcomes on a three-zone linked power system are furnished to authenticate the usefulness and advantages of the proposed technique.